New soliton solutions of Davey-Stewartson equation with power-law nonlinearity - Demiray, Seyma Tuluce; Bulut, Hasan (Springer, 2017)
This study is related to new soliton solutions of Davey-Stewartson equation (DSE) with power-law nonlinearity. The generalized Kudryashov method which is one of the analytical methods has been used for finding exact solutions of this equation. By using this method, dark soliton solutions of DSE have been found. Also, by using Mathematica Release 9, some graphical representations have been done to analyze the motion of these solutions.
Keywords: Davey-Stewartson equation; Generalized Kudryashov method; Dark soliton solutions; Mathematica Release 9